Between Self-marketing and Subversion: Web 2.0 and Its Subjects (KULT_online, 2011)
Following in the tracks of Foucault and Butler, Ramón Reichert draws a dynamic line between self-expression, self-marketing, and the subversive appropriation of the Web 2.0. By analysing the micro-processes of the Social Web, he probes for the subject of a media-driven culture of permanent application, and demonstrates a great sensibility for the structural interdependence of economy and culture. A more rigorous reflection on the theoretical assumptions would have sharpened his viewpoint, which nevertheless keeps the overheated Web debate in perspective.